E a família (empresa) como vai? - Mañas, Antonio Vico (Revista Administração em Diálogo - RAD, 2012)
Kelin E. Gersick; John A. Davis; Marion McCollon Hampton e Ivan Lansberg Negócio Editora, São Paulo, 1997 - 308 p.